Boublil and Daigle. Nietzsche and Phenomenology: Power, Life, Subjectivity. 2013 - Diogo Heber Albino de Almeida (Mutatis Mutandis: Revista Internacional de Filosofía)
A recent work organized by Élodie Boublil and Christine Daigle. Boublil is, according to the sheet at the end of the book, graduated at Sorbonne University (Paris I) and at L'Institut d'études politiques (Sciences-Po), in Paris. Currently she is a PhD candidate at McGill University, and teaches philosophy at the United Nations International School, in New York. Her studies are, in fact, about Husserl, Heidegger and Nietzsche. Daigle, in turn, is a philosophy teacher and holds the Chancellor’s Chair for Research Excellence at Brock University. Her studies are over Sartre, Simone de Beauvoir and Nietzsche. This book has the contribution of some significant authors on related studies, as – besides organizers, Rodolf Boehm, Françoise Dastur, Babette Babich Keith Ansell-Pearson, Didier Franck, Lawrence J. Hatab, Saulius Geniusas, Kristen Brown Golden Françoise Bonardel, Bettina Bergo, Frank Chouraqui and Galen A. Johnson.